Al-doping driven electronic structure of α-NiS hollow spheres modified by rGO as high-rate electrode for quasi-solid-state capacitor. Issue 24 (15th December 2022) - Yuan, Jingjing; Lu, Yuchen; Huang, Bingji; Xu, Hanqiao; Tao, Yingrui; Xu, Hui; Zhang, Wenyao; He, Guangyu; Chen, Haiqun
Abstract: Developing an optimized electronic structure of α-NiS electrode material is critical for its high-rate electrochemical performance of quasi-solid-state capacitor. Herein, Al 3+ have been doped into α-NiS lattice and the reduced graphene oxide (rGO) is employed to modify Al-doping α-NiS, to alleviate the low-mobility charge of α-NiS. The electronic structure and electrochemical properties of α-NiS hollow spheres induced by Al-doping and rGO modification are investigated, both experimental characterization and theoretical results confirm Al-doping affect the electronic structure and electrochemical performance of α-NiS hollow spheres. In the composite of Al-doping α-NiS and rGO (named as Alx Ni1-x S/rGO), the doped heteroatom improves the intrinsic electronic structure of α-NiS and the rGO provides a good electric conducting network, leading to an enhanced electrochemical performance of α-NiS as high-rate electrode material. After evaluation, the optimized Al0.2 Ni0.8 S/rGO composite shows a superior reversible capacity of 1096 C g −1 at 2 A g −1, and retains a capability of 471 C g −1 at a high-rate of 30 A g −1 . Moreover, an asymmetric quasi-solid-state hybrid capacitors assembled by Al0.2 Ni0.8 S/rGO and activated carbon presents a high energy density of 30.6 Wh kg −1 . This work provides a foundational strategy for the modification of α-NiS through Al-doping and combining with rGO, which has a positive effect on α-NiS electrode material in quasi-solid-state hybrid capacitors.